KtrAB, a New Type of Bacterial K(+)-Uptake System from Vibrio alginolyticus - Nakamura, Tatsunosuke (American Society for Microbiology, 1998)
Vibrio alginolyticus contained two adjacent genes, ktrA and ktrB, which encode a new type of bacterial K(+)-uptake system. KtrA and KtrB are peripheral and integral membrane proteins, respectively. Six of the nine sequenced bacterial genomes contain homologs to both ktrA and ktrB, suggesting that KtrAB is widespread.